Hair symbols as representations of love and loss in Nizar Qobbani's poetry: A semiotic study of Roland Barthes - Bima Sakti; Misbahus Surur; Moh. Mahrush Ali; Whida Rositama (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2026)
The study aims to demonstrate how Nizar Qabbani's poem Tauud Sya'rii Alaika uses hair as a symbol to depict love and close relationships and the experience of losing someone. The study employs Roland Barthes' semiotic framework to demonstrate how hair transforms from its basic meaning to its deeper cultural meaning. The poem uses hair as a physical body part to create a symbolic framework that conveys emotional experiences and painful memories and future aspirations. The research employed descriptive qualitative methods together with Barthes' semiotic analysis technique, which examines the signs and meanings and myths present in the poem's text. The primary data source is the poem from the Al-Hubb poetry anthology, which contains the Nizar Qabbani work about love. The secondary data sources included relevant books and scientific articles and journals. The researchers collected data through literature study and text analysis while using the Miles and Huberman model to analyze data through three steps, which included data reduction and data presentation and drawing conclusions through the verification process. The analysis shows that a woman's hair is not merely understood as a physical part of her body but rather transcends its biological dimension with her lover. Hair is presented as a symbol of love, emotional closeness, and loss, enriched by the imagery of autumn and the stars as a representation of the woman's inner journey and emotional story. This simple yet meaningful symbol is used to express the dynamics of the profound journey of love and separation between herself and her lover, while also reflecting the values and cultural traditions surrounding them.